First record of Glycymeris taylori Angas, 1879 and two additional records of Azumapecten ruschenbergerii Tryon, 1869 and Lutraria australis Deshayes, 1855 from the north west of the Persian-Arabian Gulf - Naser, Murtada D.; Yasser, Amaal Gh. (Acta Biologica Sibirica, 2023)
The northwestern Persian-Arabian Gulf marine ecoregion has several bivalves recorded. The present study is to gather new bivalve distribution data from the Iraqi shore. From 2020 to 2021, three marine bivalves were found in the northwestern Arabian Gulf, Iraqi coast. Glycymeris taylori Angas, 1879 (family Glycymerididae) recorded for the first time from the Gulf, Azumapecten ruschenbergerii Tryon, 1869 (family Pectinidae) and Lutraria australis Deshayes, 1855 (family Mactridae). These new records illustrate the need for more concentrated marine diversity studies, particularly on bivalve groups in this biodiverse region.